The use of supplementary materials in EFL classes: a comparative analysis of public and private high schools. - Paredes Vallejo, Karina Alexandra (2013)
The use of supplementary materials in English as a Foreign Language (EFL) classes: A comparative analysis of public and private high schools” is the theme of the present research whose purpose is to determine and analyze both institutions. The research was conducted in Puyo, capital of Pastaza province, from this city a public and private high school were selected; from these institutions a 1 st, 2nd, and 3rd year of senior high school were chosen respectively, in order to observe five EFL classes in each course, focusing on the supplementary materials used by the teachers. The data was collected through observation forms, questionnaires, and surveys. The data was then tabulated in charts for the quantitative and qualitative analysis taking into account aspects of pertinence, appropriateness, quality, and frequency of use of the supplementary material proposed for the current study. The results obtained show that the white board was the supplementary material mostly used in EFL classes, in both institutions.the supporting materials used in EFL public and private high schools as well as to compare how they were used in